Core Ethical Values Character Education: Based On State Philosophy - Lilis Sholihah; Sahliah Sahliah; Aan Hasanah; Bambang Samsul Arifin (Universitas Muhammadiyah Enrekang, 2023)
By oriented to the basis of the state as the basis for behavior, it is hoped that the Indonesian people will have a strong personality and character based on the ideology of the country. But the reality in Indonesia is that the moral condition is on the edge. Because Indonesia is currently experiencing a multidimensional crisis due to the influence of globalization.The purpose of writing this article is to examine the concept of Core Ethical Values of character education (based on state philosophy). Based on references and through educational studies. This study uses a descriptive qualitative approach, namely by describing data in the form of words that the author observes. The results showed that core ethical values in character education are the foundation as well as the key to the success of character education. These values are not only included in a set of educational curricula then taught by teachers, but transformed in the individual's living culture. The character understood consists of three interrelated components, namely knowing the good, loving or desiring the good, and acting the good. Pancasila is a state ideology which is the result of deep thoughts from national leaders in the past who have tried to find the right ideological concept for the Indonesian nation, which contains the principle of life in the nation and state based on the one and only god, humanity that is just and civilized, Indonesian unity, citizenship led by wisdom in representative consultation and social justice for all Indonesian people. As for the character expected by individuals who are imbued with the precepts of Pancasila, Characters that come from the heart, including faith and piety, honest, trustful, fair, orderly, obey the rules, responsible, empathize, dare to take risks, never give up, willing to sacrifice, and patriotic spirit, then Characters sourced from sports thinking include intelligent, critical, creative, innovative, curious, productive, science and technology-oriented, and reflective and characters sourced from sports (kinesthetics) including clean, and healthy, sportsmanship, tough, reliable, endurance, friendly, cooperative, determinative, competitive, cheerful, and persistent.